Upaya Meningkatkan Prestasi Belajar Siswa Kelas XI TB.2 PPKN Melalui Metode Pembelajaran Kooperatif Jigsaw - Zuraidah (Yana Research, 2023)
The journey has been winding and full of challenges since its formation until its current state which has made history an interesting study material. Moreover, recently there has been a group of people who doubt the existence of PPKn. Due to the many abuses and betrayals of Pancasila and Citizenship Education, complete human development has been hampered. And there are also those who question the success of PPKn teaching on the morals of students in particular and the wider community in general. This research uses three rounds of action research. Each round consists of 4 stages, namely: design, activities and observations, reflection and revision. The target of this research is class XI students. TB 2. Civics academic year. The data obtained is in the form of formative test results, observation sheets of teaching and learning activities. From the results of the analysis, it was found that student learning achievement increased from cycle I to cycle III, namely, cycle I (67.44%), cycle II (79.01%), cycle III (90.70%). The conclusion of this research is that cooperative learning methods can have a positive influence on the achievement and learning motivation of class XI.TB.2 students and this learning model can be used as an alternative for PPKn learning. This research was carried out at SMKN Meukek, South Aceh Regency.